Journal club: An Important Teaching-Learning Activity (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Journal club is an important teaching learning activity of educational institutions and thus improving medical education of the country. It is directly related to improving patients outcome of one,s own department or institution. There is increasing demands to practice effectively medical science at highest stakes. A formal journal club facilitates discussing and evaluating new research and its application to practice and improving patient care. However many a times, journal club fails to achieve its role and a superficial discussion on clinical aspects distracts its aims and objectives. The advantages of using a journal club are that you and your peers can keep current with new transplant knowledge, learn to facilitate the strength of the evidence, promote implementation of new knowledge into practice, and improve patient outcomes. A journal club has been defined an educational meeting in which a group of individuals discuss current articles, providing a form for a collective effort to keep up with the literatures Key words: Journal club, Evidence based practice, Medical education.J Bangladesh Coll Phys Surg 2015; 33(4): 213-217